The Impact of Gadget Use on Adolescents: a Literature Review - Vuriyanti, Mega; Rahmawati, Iis; Suhari, Suhari (Universitas Malahayati, 2024)
ABSTRACT The use of gadgets by adolescents without balanced knowledge will impact health. The purpose of this study is to analyze the impact of gadgets on adolescents so that the impact of using gadgets can be prevented and minimized. This research method uses a literature review. Where in the process of searching for literature in this literature review using Pubmed, Scopus, Proquest, and Google Scholar databases with a range of published years 2019-2024. The search was done using several keywords